Assessment of Body Weight and Scrotal Circumference as Determinants of Semen Production Traits in Kankrej Bulls Using a Mixed Model Approach - Dangar, Nikhil S.; Brahmkshtri, Balkrishna P.; Pandya, Gaurav M.; Patel, Prakash B. (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present study was conducted to evaluate the influence of body weight (BW) and scrotal circumference (SC) at the time of semen collection on semen production traits in Kankrej bulls. A total of 1307 ejaculates collected from 26 Kankrej bulls maintained at the Dama Semen Production Unit, Gujarat, were analyzed. The semen production traits studied included semen volume, sperm concentration, and number of semen doses per ejaculate. Data were analyzed using a linear mixed model with Restricted Maximum Likelihood (REML) method, considering BW and SC as fixed effects and bull as a random effect. The overall least squares means for semen volume, sperm concentration, and number of semen doses per ejaculate were estimated as 5.90 ± 0.30 mL, 1302.83 ± 48.66 million/mL, and 335.36 ± 20.58, respectively. BW at semen collection had a highly significant (p
Keywords: Body weight; Kankrej bulls; Scrotal circumference; Semen traits